Association between HTR2C gene variants and suicidal behaviour: a protocol for the systematic review and meta-analysis of genetic studies - Thelma Beatriz, González-Castro (BMJ Publishing Group, 2014)
INTRODUCTION: Suicide is an important public health problem and one of the most common causes of death throughout the world. Suicidal behaviour is complex, and its causes are multifactorial. Case–control studies have reported an association between an alteration of the serotonin system and suicidal behaviour. Recently, it has been suggested that the 5-HTRC2 serotonin receptor gene is involved in the pathogenesis of suicidal behaviour. METHODS AND ANALYSIS: To evaluate the role of the 5-HTR2C gene in suicidal behaviour, we will perform a systematic review and a meta-analysis of worldwide reports that have investigated the association between the serotonin system and suicidal behaviour. This analysis will be reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. Studies deemed fit for inclusion in the systematic review will be scored for methodological quality using the Newcastle-Ottawa Assessment Scale (NOS). The inclusion criteria will be to present independent data, to be case–control studies and to be published in journal peer reviews. To generate more accurate analyses, we will grade the reports using the GRADES scale procedures. ETHICS AND DISSEMINATION: This study will describe the association between the HTR2C gene and suicidal behaviour. The results will be reported in a peer-reviewed publication and in scientific presentations in Mexico and throughout the world. TRIAL REGISTRATION NUMBER: PROSPERO CRD42014009213.